Estimating Dispersal and Survival of Anopheles gambiae and Anopheles funestus Along the Kenyan Coast by Using Mark–Release–Recapture Methods - Midega, J.T.; Wilson, M.D.; Mbogo, C.M.; Mwambi, H.; Ojwang, G.; Mwangangi, J.M.; Nzovu, J.G.; Githure, J.I.; Guiyun Yan, G.; Beier, J.C. (Journal of Medical entomology 44(6): 923-929, 2007)
Mark-release-recapture (MRR) experiments were conducted with emerging Anopheles gambiae s.l. and Anopheles funestus Giles at Jaribuni and Mtepeni in Kilifi, along the Kenyan Coast. Of 739 and 1,246 Anopheles released at Jaribuni and Mtepeni, 24.6 and 4.33% were recaptured, respectively. The daily survival probability was 0.96 for An. funestus and 0.95 for An. gambiae in Jaribuni and 0.83 and 0.95, respectively, in Mtepeni. The maximum flight distance recorded was 661 m. The high survival probability of An. gambiae and An. funestus estimated accounts for the continuous transmission of malaria along the Kenyan coast. This study also shows that the release of young, emergent female Anopheles improves the recapture rates and may be a better approach to MRR studies.
Keywords: Anopheles gambiae; Anopheles funestus; Mark-release-recapture; Dispersal; survival probability